#TITLE_ALTERNATIVE# - PUTRI RUDIAWAN (NIM 12903007), AMANDA
Maximum Cross Correlation (MCC) is one method that can be applied to retrieve sea surface current. MCC technique here is applied in the South Java Seas in term of sea surface temperature (SST) images from NOAA satellite. In this study, NOAA 2006 images are used except for March, August, and December and the resulting currents are compared to the currents from TOPEX. Results have shown that inferred MCC currents correspond quite well to the currents derived from TOPEX satellite. The deviation of the MCC vectors from the TOPEX vectors is expressed as percentage errors mean of direction and velocity components and they are 17.644% and 21.264% with each have range of 10.379%-35.658% and 3.455%-33.376%. This method yielded surface currents that have more detail resolution compared to currents obtained from the TOPEX imagery with ratio 1.1 : 27.75 km, therefore those can show local and regional current like South Java Current in June. Surface currents derived from this method are estimated as currents dominated by influence of local surface wind.